Helping Children Experiencing Difficulties in Learning to Read Kiswahili: Perspectives of pre-primary teachers in Tanzania - Richard, Shukia (Papers in Education and Development, 2018)
The study sought to ascertain the beliefs held by pre-primary teachers about why some children experience difficulties in learning to read Kiswahili and how they can be helped. Knowing about teachers ' beliefs is a gateway to improving pre-primary reading instruction, the curriculum and learning to read early. The study was informed by the qualitative hermeneutic-phenomenology methodology, comprising 21 semi-structured interviews and 12 classroom observations. The findings reveal that although teachers were uncertain about what caused children ' s learning difficulties they cited factors both internal and external to the child which were outside the teachers ' realm. Moreover, teachers believed in supplemental practices, parents ' involvement, retention, forming mixed-ability groups in class, focusing on the 3Rs (reading, writing and arithmetic) and in-service teacher training as a ' toolkit ' to help children who are finding learning to read difficult. The study recommends that teachers ' professional development programmes should be on-going and that a systematic diagnostic mechanism is established to identify children with learning difficulties. Keywords: Teachers ' beliefs, finding learning to read difficult, pre-primary teachers